Fraturas de caminhos ótimos - Lima, André de Albuquerque (2023)
Traffic congestion in developed cities is a problem that causes financial and public health losses. The present work seeks through the OPC (Optimal Path Cracks) algorithm to understand which points are most vulnerable to the formation of congestion and which factors influence these vulnerabilities. OPC finds optimal paths and then blocks the site of greater weight along the way, in order to understand how the optimal paths of the network are rearranged as the sites of greater weight are blocked. For this, firstly, a review of Graph Theory is made, focusing on Dijkstra’s algorithm to find optimal paths in a network. Next, we apply the OPC model to the city of Fortaleza, with results compared to those found in the literature when the algorithm is applied to other cities, particularly Boston and Manhattan in New York. Furthermore, the obtained results indicate that the most vulnerable sections of the city are concentrated in 3,7% of the total segments. Thus, the algorithm was capable of identifying the sections where an intervention would be most effective in reducing congestion in the city, thereby demonstrating its viability for studying urban traffic.